PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN PENGGUNAN, DAN PERSEPSI RISIKO TERHADAP MINAT MENGGUNAKAN LAYANAN UANG ELEKTRONIK (Studi Kasus pada Masyarakat di Kota Semarang) - Singgih Priambodo; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2016)
This study is a replication and development model of the Technology Acceptance Model (TAM) to determine the effect of perceived usefulness, perceived ease of use and the perception of risk toward users intention to use electronic money services on users of electronic money in Semarang. This type of research is using explanatory research. Data collection techniques through questionnaires using convenience sampling with sample of 100 respondents as data samples. The data were analyzed quantitative, consist of evaluation outer and inner models using software SmartPLS 2.0 M3. The results of this study conclude that the perception of usefulness has a positive and significant effect on the intention to use e-money services, perceived ease of use has a positive and significant impact on the intention to use e-money services, perceived of risk have a negative and significant impact on the intention to use e-money. The suggestions that can be given in this study to the issuer of electronic money is to increase intention to use of electronic money by increasing the benefits and ease of use electronic money through cooperation with various merchants. Electronic money issuers must improve the quality and security of electronic money in order to reduce the level of risk of the use of electronic money.